Pre-hospital care: characterization of the care of a brazilian city (Research, Society and Development, 2022)
Objective: To characterize the care provided in pre-hospital care. Methodology: Quantitative, cross-sectional, study conducted at the Mobile Emergency Care Service (SAMU) in a Brazilian city, in October and November 2018. Identified 340 occurrences that generated 297 visits. Results: Results: More than half of the visits occurred at home 236 (79.5%) and in the hospital The highest number of visits occurred in the health district of Tirirical 60 (20.2%). Intervals of less than one (1) minute between the communication of the radio operator to the health team and the departure of the ambulance 215 (72.4%), times less than 20 minutes referring to the departure of the ambulance to the arrival at the site 193 (65%) and departure from the place and destination 163 (54.9%). A longer delay was identified in psychiatric care and simple complaints, such as diarrhea and vomiting Only 39 visits had the risk classified, 27 (69.2%) green, 7 (18%) red, 5 (12.8%) and all visits classified as red were assisted by advanced life support. The hospital predominated 244 (82.2%) as the outcome of the victims and 15 (5.1%) died at the site. Conclusion: The success of the care of a victim in a situation of urgency and emergency depends primarily on the time factor.